English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

log(sub)2 x + log(sub)2(x-2) - log(sub)2(x-3) = 3
log(sub)2 [x(x-2)/(x-3)] = 3
(x^2 - 2x)/(x-3) = 2^3=8
x^2 - 2x = 8x - 24
x2 - 10x + 24 = 0
(x-6)(x-4) = 0

x=6, 4

2007-06-10 08:00:01 · 3 answers · asked by jill b 1 in Science & Mathematics Mathematics

3 answers

It is easier to read if you write it like this:

log2(x) meaning log base 2 of x

Anyway...

log2(x) + log2(x - 2) - logx(x - 3) = 3

log2[(x(x - 2))/(x - 3)] = 3

2^3 = (x^2 - 2x)/(x - 3)
8 = (x^2 - 2x)/(x - 3)
8(x - 3) = x^2 - 2x
8x - 24 = x^2 - 2x
0 = x^2 -10x + 24
0 = (x - 4)(x - 6)

x = 4, 6

Yes, you are correct.

2007-06-10 08:08:10 · answer #1 · answered by its_victoria08 6 · 0 0

It looks right

2007-06-10 15:05:03 · answer #2 · answered by mendelbrot 1 · 0 0

Right on. Very Good. Well done!!

2007-06-10 15:04:45 · answer #3 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers